School Management In Improving The Quality of Education in Basic Education - Berlianti, Anggun Nabila; Prasista, Elsa Leila Trisna; Azizah, Zulfati; Deadonita, Vriantika; Zulfa, Itsfa Naily (Jurnal Inovasi Pembelajaran Karakter, 2024)
School administration encompasses all aspects of overseeing the educational process to accomplish pre-established objectives, including short, medium, and long-term goals. The goal of this study is to determine how school administration is raising the standard of instruction, which includes: (1) program planning; (2) program implementation in school; (3) challenges encountered. Descriptive methods and a qualitative approach were employed in this study, and documentation studies and observation interviews were used to gather data. Teachers, supervisors, and principles of SD Negeri Karanganyar served as the research subjects. It is anticipated that supervisors will be able to guide and oversee school administrations in raising the standard of instruction on the planning of school apps, their implementation, and the challenges they encounter in a timely, effective, and efficient manner so that the quality of education in these schools can improve..